Effects of the mindfulness program for male substance abusers in Thailand on stress, deliberate self-harm, and drug abstinence intention: A repeated-measure design - Singtakaew, Arunothai; Chaimongkol, Nujjaree; Puangladdac, Skaorat; Wongpiromsarn, Yongyud (Belitung Nursing Journal, 2024)
Background: Substance abuse is prevalent among males, and mindfulness could serve as a means of helping individuals suffering from the adverse effects of substance abuse find relief. Objective: This study employed a one-group repeated-measure design and aimed to evaluate the effects of the mindfulness program on stress, deliberate self-harm, and drug abstinence intention among male substance abusers. Methods: The mindfulness program was implemented for Thai males with a history of narcotic drug use. Five participants were recruited from a rehabilitation institute in Thailand using convenience sampling. The program consisted of eight sessions over four weeks. The study outcomes were measured at three time points: pre-intervention (Time 1, Week 1), post-intervention (Time 2, Week 4), and follow-up (Time 3, Week 6). Research instruments included the Deliberate Self-Harm Inventory, the Perceived Stress Scale, and the Drug Abstinence Intention Questionnaire, all of which had Cronbach’s alpha values above 0.80. Data analysis was carried out using the Friedman test and Dunn-Bonferroni post-hoc test. Results: The eight-session program was implemented as intended, with a retention rate of 100%. The mean scores of deliberate self-harm and drug abstinence intention were significantly different across the three time points (χ2 = 10.000 and χ2 = 9.579, p <0.01, respectively). After conducting pairwise comparisons, the mean scores of deliberate self-harm at Time 2 and Time 3 were significantly lower than those at Time 1. Additionally, the mean scores of drug abstinence intention at Time 2 and Time 3 were higher than those at Time 1. However, the mean score of stress did not have a significant difference. Conclusion: This program was both acceptable and effective in reducing deliberate self-harm and improving drug abstinence intention. These findings suggest that nurses and healthcare teams involved in caring for individuals with substance abuse issues could utilize this intervention alongside other therapies or hospital treatments. Consequently, relapse prevention among substance abusers could be achieved. Thai Clinical Trials Registry Number: TCTR20230404001